Presessions to the National Diabetes Prevention Program May be a Promising Strategy to Improve Attendance and Weight Loss Outcomes. Issue 2 (February 2019) - Ritchie, Natalie D.; Kaufmann, Peter G.; Gritz, R. Mark; Sauder, Katherine A.; Holtrop, Jodi Summers
Purpose: The National Diabetes Prevention Program (NDPP) is a widely disseminated lifestyle intervention. Attendance is problematic, leading to suboptimal weight loss, especially among racial/ethnic minority participants. We conducted a novel "presession" protocol to improve engagement of diverse NDPP candidates, comparing NDPP participants who attended a presession to those who did not on attendance and weight loss outcomes. Design: Longitudinal cohort study. Setting: A safety net health-care system. Participants: A total of 1140 patients with diabetes risks (58.9% Hispanic, 19.8% non-Hispanic black, 61.8% low income). Intervention: The NDPP has been delivered in a Denver, Colorado health-care system since 2013. The program included 22 to 25 sessions over 1 year. Beginning September 2016, individuals were required to attend a presession before enrollment that focused on (1) increasing risk awareness, (2) motivational interviewing to participate in the NDPP, and (3) problem-solving around engagement barriers. Measures: Duration and intensity of NDPP attendance and weight loss. Analysis: Outcomes of 75 presession participants who enrolled in the NDPP were compared to 1065 prior participants using analysis of covariance and multivariable logistic regression. Results: Presession participants stayed in the NDPP 99.8 days longer ( P < .001) and attended 14.3% more sessions ( P < .001) on average than those without a presession. Presession participants lost 2.0% more weight ( P < .001) and were 3.5 times more likely to achieve the 5% weight loss target ( P < .001). Conclusion: Presessions may improve NDPP outcomes for individuals from diverse backgrounds. A full-scale trial is needed to determine whether presessions reliably improve NDPP effectiveness.